Realisme Kritis Roy Bhaskar: ‘Pelayan’ Filosofis untuk Ilmu-Ilmu Sosial Emansipatoris - Muhammad Nurul Huda (Muqoddima Jurnal Pemikiran dan Riset Sosiologi, 2020)
This article aims to introduce Roy Bhaskar's philosophical system known as critical realism. The focus will be directed to the three phases of development in the Roy Bhaskar philosophical system, by putting each phase as response to the problems in the philosophy of science and the mainstream Western philosophical tradition as well as social and humanitarian problems in general. This article was compiled using a literature-based analysis, by examining the Bhaskar’s works as well as its proponents and critics. Based on the analysis, I argue that Roy Bhaskar's philosophy provides a solid foundation of thinking for the social and human sciences, especially for emancipatory social sciences. Bhaskar’s critical realism restores the ontological dimension of science and subsequently the deep ontology dimension of our world, which is removed and ignored by mainstream Western philosophical traditions, both modern and contemporary. The commitment to the ontology of science and the deep ontology of the world produces a more adequate foundation for social and human sciences and the possibility for the realization of human self-emancipation projects.